Higher Human Cytomegalovirus (HCMV) Specific IgG Antibody Levels in Plasma Samples from Patients with Metastatic Brain Tumors Are Associated with Longer Survival - Peredo-Harvey Inti; Bartek Jiri; Ericsson Christer; Yaiw Koon-Chu; Nistér Monica; Rahbar Afsar; Söderberg-Naucler Cecilia (MDPI, 2025)
Background: Human cytomegalovirus (HCMV) has been detected in tissue samples from patients with glioblastoma but little is known about the systemic immunological response to HCMV in these patients.
Objectives: To investigate the presence and clinical significance of HCMV antibodies levels in plasma samples obtained from patients with brain tumors.
Materials and Methods: HCMV-specific IgG and IgM antibody levels were determined in 59 plasma samples collected from brain tumor patients included in a prospective study and in 114 healthy individuals. We examined if the levels of HCMV specific antibodies varied in patients with different brain tumor diagnoses compared to healthy individuals, and if antibody levels were predictive for survival time.
Results: HCMV specific IgG antibodies were detected by ELISA in 80% and 89% of patients with GBM and astrocytoma grades II-III, respectively, in all samples (100%) from patients with secondary GBM and brain metastases, as well as in 80% of healthy donors (n = 114). All plasma samples were negative for HCMV-IgM. Patients with brain metastases who had higher plasma HCMV-IgG titers had longer survival times (p = 0.03).
Conclusions: HCMV specific IgG titers were higher among all brain tumor patient groups compared with healthy donors, except for patients with secondary GBM. Higher HCMV specific IgG levels in patients with brain metastases but not in patients with primary brain tumors were associated with prolonged survival time.